PEMBERDAYAAN EKONOMI MASYARAKAT BERBASIS MASJID Studi Kasus di Masjid Baiturrahman Klidon Sinduharjo Ngaglik Sleman - Muslim, Azis (Da'wa and Communication Faculty State Islamic University Walisongo, Semarang, Indonesia, 2014)
In Indonesia todays, the number of mosques, according to the Indonesian Council of Mosques, is no less than 700 thousand mosques. This number represents the greatest number of mosques in the world. From the large number of those, only a small portion has still been developed for handling poverty problems. Based on ths issue, it is necessary examine the Baiturrahman Mosque in Klidon Sinduharjo Ngaglik Sleman. This study will investigate and describe the success of economic empowerment achieved by the mosque, especially in tackling the poverty problems among the surrounding congregation of societies. The study shows that the managements of Baiturrahman mosque operate some stages in empowering the local economy. First, they build management phases, such as building the perception of stakeholders regarding the mosque function, managing the mosque in accordance with modern management, and building success dreams. Second, they apply the management principles, such as serving the congregations, making innovation and creativity for them, giving and enhancing the congregations rule in the mosque. Third, they choose the right strategy, such as starting to do the simplest and easiest thing, as well as considering the ongrgations’ interests. ****Di Indonesia, jumlah masjid menurut Dewan Masjid Indonesia tidak kurang dari 700 ribu masjid. Jumlah ini merupakan jumlah terbesar dari masjid di dunia. Dari jumlah tersebut, hanya sebagian kecil masih dikembangkan untuk menangani masalah kemiskinan. Berdasarkan masalah tersebut, perlu melihat Masjid Baiturrahman di Klidon Sinduharjo Ngaglik Sleman. Peneliti-an ini akan menyelidiki dan menggambarkan keberhasilan pemberdayaan ekonomi yang dicapai oleh masjid, terutama dalam menanggulangi masalah kemiskinan di antara jama’ah sekitar masyarakat. Studi ini menunjukkan bahwa manajemen masjid Baiturrahman mengoperasikan beberapa tahapan dalam memberdayakan ekonomi lokal. Pertama, membangun manajemen, seperti membangun persepsi stakeholders mengenai fungsi masjid, mengelola masjid sesuai dengan manajemen modern, dan mimpi membangun kesuksesan. Kedua, menerapkan prinsip-prinsip manajemen, seperti melayani jama’ah, membuat inovasi dan kreativitas bagi mereka, memberikan dan meningkatkan jama’ah di masjid. Ketiga, memilih strategi yang tepat, seperti mulai melakukan hal yang sederhana dan mudah, serta mempertimbangkan kepentingan organisasi.